A Highly Sensitive Flexible Capacitive Tactile Sensor with Sparse and High‐Aspect‐Ratio Microstructures. (1st March 2018) - Wan, Yongbiao; Qiu, Zhiguang; Hong, Ying; Wang, Yan; Zhang, Jianming; Liu, Qingxian; Wu, Zhigang; Guo, Chuan Fei
Abstract: Highly sensitive flexible tactile sensors that can be fabricated in a low cost and efficient way are in great demand for intelligent soft robotics and friendly human–machine interaction. Herein, a highly sensitive flexible tactile sensor is developed by using bionic micropatterned polydimethylsiloxane (m‐PDMS) replicated from lotus leaf. The m‐PDMS substrate consists of high‐aspect‐ratio and low‐density microtowers, and is covered by ultrathin silver nanowires as a bottom electrode. The capacitive sensing device is constructed by sandwiching the bottom electrode, a colorless polyimides dielectric layer, and a top electrode, and exhibits a high sensitivity of ≈1.2 k Pa −1, a ultralow limit of detection <0.8 Pa, and a fast response time of 36 ms. The finite‐elemental analysis indicates that the sparse and high‐aspect‐ratio microtowers are critical to achieve high sensitivity, low limit of detection, and fast response to external stimulus. The flexible tactile sensor also exhibits high robustness: it can be tested for at least 100 000 cycles without showing fatigue. More importantly, the flexible tactile sensors are potentially useful in intelligent soft robots, health monitoring, and motion detection. Besides, the fabrication strategy may offer a guideline to design other microstructures for improving the performance of flexible tactile sensors. Abstract : High‐aspect‐ratio and low‐density microtowers replicated from lotus leaf are applied in a capacitive tactile sensor. The device exhibits a high sensitivity of 1.2 k Pa −1, a low limit of detection <0.8 Pa, and a fast response time of 36 ms. Flexible tactile sensors are potentially useful in intelligent soft robots, health monitoring, and motion detection.